Long-term survivors following autologous haematopoetic stem cell transplantation have significant defects in their humoral immunity against vaccine preventable diseases, years on from transplant. Issue 34 (9th August 2021) - Colton, Hayley; Greenfield, Diana M.; Snowden, John A.; Miller, Paul D.E.; Morley, Nicholas J.; Wright, Josh; Darton, Thomas C.; Evans, Cariad M.; de Silva, Thushan I.
Highlights: Vaccination programmes are recommended post-HSCT but poorly completed. Almost all of our cohort had inadequate diphtheria and pneumococcal antibody titres. Targeted "catch-up" vaccination resulted in an increase in antibody titres. Universal diphtheria and pneumococcal vaccination may be practical in similar cohorts. Targeted measles and VZV vaccination could be given based on serostatus. Earlier strategies to optimise immunity in autologous HSCT patients are warranted. Abstract: Current international guidelines recommend routinely vaccinating haematopoetic stem cell transplant (HSCT) recipients. Despite significant infection-related mortality following autologous HSCT, routine vaccination programmes (RVP) completion is poor. For recovered HSCT recipients, it is uncertain whether catch-up vaccination remains worthwhile years later. To determine potential susceptibility to vaccine preventable infections, we measured antibody titres in 56 patients, a median of 7 years (range 0–29) following autologous HSCT, who had not completed RVP. We found that almost all participants had inadequate titres against diphtheria (98.2%) and pneumococcal infection (100%), and a significant proportion had inadequate titres against measles (34.5%). Of those subsequently vaccinated according to available guidelines, many mounted adequate serological responses. These data suggest a pragmatic catch-up approach for autologous HSCT recipients who have not completed RVP is advisable, with universal vaccination against some pathogens (e.g. Streptococcus pneumoniae and diphtheria) and serologically-guided approaches for others (e.g. measles and varicella zoster virus).